A double perovskite-based red-emitting phosphor with robust thermal stability for warm WLEDs. Issue 11 (1st August 2020) - Mao, Qinan; Shen, Biao; Yang, Tao; Zhong, Jiasong; Wu, Guoqiang
Abstract: Red-emitting Ba2 YSbO6 :Eu 3+ phosphors with double perovskite structure have been prepared by solid-state method. Phase structures, photoluminescence properties, and thermal stability performances have been investigated in detail. The prepared phosphors reveal a cubic phase with the space group of Fm-3m. They exhibit a doughty red emission band at 612 nm ascribed to the Eu 3+ : 5 D0 → 7 F2 transition under 393 and 465 nm excitation. The samples have high concentration quenching property with the optimal concentration reached to 70 mol%, deriving from the quadrupole-quadrupole interaction. Additionally, the Ba2 YSbO6 :Eu 3+ phosphors demonstrate robust thermal performance with the emission intensity retaining 78.8% at 423 K of that at 303 K. Ultimately, the phosphor-converted LED device is fabricated by combining the red-emitting Ba2 YSbO6 :Eu 3+ phosphor and YAG:Ce 3+ yellow ones to a blue chip (460 nm), which exhibits a warm white light with color rendering index(CRI) of 80.8 and correlated color temperature (CCT) of 5184 K.